The effect of exercises according to the principle of angular momentum to develop technical performance on the horizontal bar apparatus for youth (Global Scientific Review, 2024)
The importance of the research and here lies the importance of the research in developing the technical performance on the horizontal bar using exercises according to the principle of angular momentum, which relied on the direct link between biomechanics and gymnastics, as it focuses on developing the technical performance by focusing on strength and accuracy as well as the body's balance on the device as a result of its reliance on the arms, this is from the biomechanics side, but from the gymnastics side, it is one of the basic movements on this device, which can be considered one of the special requirements that enhance its ability to control during rotational movements with the modern trend of training towards linking these movements with other movements to obtain higher difficulty, but the problem of the research is that traditional training programs may lack focus on the principle of angular momentum as a basic factor for developing the skills of the horizontal bar, which hinders young people from achieving the ideal performance that this device requires, and from here the need arises to design special exercises based on the principle of angular momentum to improve the ability of young people to perform dynamic movements with greater accuracy and stability, which made mastering these skills take a long time in training to master the skills required for each device, especially the youth stage, and the objectives of the research were to prepare exercises according to the principle of angular momentum to develop the technical performance on the horizontal bar for players of the specialized center For gymnastics aged (16-18) years, and to identify the statistical differences in technical performance on the horizontal bar for players of the Specialized Center for Gymnastics aged (16-18) years between the pre-test and post-test. As for the research methodology, the researcher adopted the experimental method with a single-group design, which is consistent with the nature of the research problem. The research community was determined intentionally, as the research community included players of the Specialized Center for Gymnastics in Dhi Qar Governorate aged 16-18 years, who represent the youth category and their number is (6) players, and they were all chosen to represent the research sample at a rate of (100%) of the original community. One of the most important conclusions is that exercises according to the principle of angular momentum developed technical performance by achieving a balance between strength and flexibility for all the skills of the horizontal bar for the research group